Os desafios de implementação dos veículos autônomos no cenário brasileiro - Cantamessa, Claudio (2022)
The most recent innovations, accompanied by cultural and socioeconomic transformations that are taking place all over the world, open the door to new scenarios of sustainable mobility. The challenge of innovation in the transport sector is represented by the automation of vehicles: Autonomous Vehicles (AVs). This report explores the resources of AVs and their relationship to mobility planning in cities, focusing especially on the technology of these vehicles and the legislation involved in using this type of vehicle in Brazil. When implementing AVs in cities, risks and benefits are foreseen, such as changes in accident rates, congestion and pollution. These factors are directly linked to the attention and approach of governments and legislators on the issue of the use of AVs. This study is mainly motivated by the absence of discussions in the Brazilian context, whether in terms of traffic legislation or the complex legal and regulatory structure that places Brazil in the last posistion of discussions and tests of AVs.